Effect of Manure and Biochar Treatment on Soil Respiration and Corn (Zea mays L.) Production in Ultisol Soil - Arif Syaifudin; Henrie Buchari; Dedy Prasetyo; Jamalam Lumbanraja (Journal of Tropical Upland Resources (J. Trop. Upland Res.), 2022)
Efforts to increase corn production can be done by improving soil fertility. Fertility level can be seen from the activity of microorganisms in the soil through the measurement of soil respiration rate. This research aimed to study the effect of chicken manure and rice husk biochar on soil respiration and maize production, and to study the correlation between soil respiration and crop production, soil moisture content, soil temperature, soil pH, and soil organic C. This research method uses a non-factorial Randomized Block Design (RAK) with 4 treatments and 4 replications, so that 16 experimental units were obtained. The data were analyzed by analysis of variance and continued with the 5% BNT test, and the correlation test between soil respiration and other observed variables was carried out. The results of this study showed that: (1) The addition of chicken manure and rice husk biochar had a significant effect on soil respiration at 10 DAP and after harvest (115 DAP), and had a significant effect on oven-dried shell weight. (2) The treatment also significantly affected the C-organic soil at 45 DAP, but had no significant effect on soil temperature, soil moisture content and soil pH in all observations. (3) There is a positive correlation between soil pH and soil respiration, but there is no correlation between soil respiration and soil moisture content, soil temperature, C-organic soil, and maize production.